2008
DOI: 10.1093/jat/32.8.673
|View full text |Cite
|
Sign up to set email alerts
|

Free Oxycodone Concentrations in 67 Postmortem Cases from the Hennepin County Medical Examiner's Office

Abstract: Heart blood free oxycodone concentrations in oxycodone-related and mixed drug overdose deaths were compared with those found incidentally at autopsy in medical examiner cases. Between 2000 and 2005, 67 oxycodone-positive postmortem cases were identified. Thirty of 67 cases (44.8%) were determined to be drug overdoses. Oxycodone alone was responsible for 7 of the 30 (23.3%) overdose deaths. Mean (median) oxycodone concentrations were 1.060 mg/L (0.824 mg/L) with a range of 0.270-3.390 mg/L. Three cases were acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Both ethanol and opioids cause respiratory depression and oversedation, potentially lethal adverse effects, and synergism can be supra-additive. Expanding the use of oxycodone has led to a higher count of unintentional overdose deaths [164]; simultaneous use of alcohol may further add to this risk [165].…”
Section: Coadministration Of Oxycodone With Ethanolmentioning
confidence: 99%
“…Both ethanol and opioids cause respiratory depression and oversedation, potentially lethal adverse effects, and synergism can be supra-additive. Expanding the use of oxycodone has led to a higher count of unintentional overdose deaths [164]; simultaneous use of alcohol may further add to this risk [165].…”
Section: Coadministration Of Oxycodone With Ethanolmentioning
confidence: 99%
“…Multiple postmortem analyses have shown that individuals who consumed opioids such as heroin along with alcohol died from blood opioid concentrations measuring significantly lower than those who died from an opioid without alcohol consumption (Darke and Hall, 2003). Additionally, a separate study that specifically investigated oxycodone-related overdoses reported that deaths resulting from the combined intake of oxycodone and ethanol were ruled to be exclusively accidental, rather than intentional (Thompson et al, 2008). Although it is possible that a general lack of awareness exists among opioid users regarding the dangers related to coconsumption of ethanol with opioids, it is likely that these individuals experience some enhancement of opioid effects when used together, leading to riskier drug-taking behavior to offset the tolerance(s) developed to the opioids.…”
Section: Introductionmentioning
confidence: 99%
“…For drug analyses in the laboratory, all chemicals were of analytical grade (Sigma‐Aldrich, St. Louis, MO, USA) unless noted. Free and total opioids were quantified for codeine, morphine, hydrocodone, hydromorphone, along with free oxycodone and free oxymorphone, as previously described , using an Agilent GC/MS (6890/5973) equipped with a DB‐5 capillary column. Briefly, after glucuronide treatment (blood total opioids only) and solid‐phase extraction (Clean Screen, United Chemical Technologies, Inc., Bristol, PA, USA), samples were derivatized with N,O‐Bis(trimethylsilyl)trifluoroacetamide (BSTFA).…”
Section: Methodsmentioning
confidence: 99%
“…The interpretation of postmortem opioid concentrations in urine, blood, and tissues is complex, and numerous studies have examined this in various settings, including death investigations . Opioid concentrations measured following appropriate therapeutic, prescription use guided by providers can overlap with abusive or illicit use.…”
mentioning
confidence: 99%